The leadership lexicon : a handbook of leadership competencies with skills and development action - Bellingham, Richard; O'Brien, William (HRD Press, 2005)
What is leadership? Simply stated, leadership is the art of getting others to want to do what you believe needs to be done. Leaders gain the confidence of others through their insights, their interpersonal influence, and their competence. Leadership is not about having the power and influence to command those who are subordinate to you. Leadership is a choice any person can make in the moment. What do leaders rely on? Effective leaders need input, processing, and feedback. They need to listen to others: their employees, their peers, their customers, their critics, their shareholders. Leaders need to be open to information of all types: positive, negative, and neutral. Leaders need processing capabilities to discriminate good from bad ideas. They need to generate new responses to changing conditions, and to create new environments for change. This book provides a solid construct for processing information (identify, build, and drive) and a wealth of ideas for generating new responses (107 competencies).